Contrast-enhanced endoscopic ultrasound for differential diagnosis of autoimmune pancreatitis: a meta-analysis - Zhu, Shanshan; Cao, Xinguang; Nabi, Ghulam; Zhang, Fangbin; Liu, Ping; Zhang, Jingwen; Guo, Changqing (Endoscopy International Open, 2024)
Background and study aims To assess the diagnostic value of contrast-enhanced endoscopic ultrasound (CE-EUS) for autoimmune pancreatitis and other solid pancreatic masses.Patients and methods A systematic search of PubMed, Embase, and Web of Science was performed from inception to October 2022. We calculated individual and pooled sensitivities and specificities to determine the diagnostic ability of CE-EUS. In addition, we calculated I2 to test for heterogeneity and explored the source of heterogeneity by meta-regression analysis.Results A total of 472 patients from seven eligible studies were included. The mean sensitivity and specificity of the Bivariate analysis were 0.84 (95% CI 0.71–0.92) and 0.95 (95% CI 0.84–0.99), respectively. The diagnostic advantage ratio was 107.91 (95% confidence interval [CI] 22.22–524.13), and the area under the summary receiver operating characteristics curve was 0.91 (95% CI 0.88–0.93). The overall heterogeneity of the studies is negligible (I2=0, 95% CI 0–100). However, notable heterogeneity was observed in the combined specificity (P <0.01, I2=74.82) and diagnostic odds ratio (P=0.05, I2=51.54). The heterogeneity in these aspects could be elucidated through sensitivity analysis.Conclusions Our analysis showed that CE-EUS is useful in identifying autoimmune pancreatitis. However, further large sample size, multicenter, prospective studies are needed to demonstrate its utility.
Keywords: Pancreatobiliary (ERCP/PTCD); Pancreatoscopy; Endoscopic ultrasonography